Hill, Fanny Christina (audio interview #3 of 4) - Hill, Fanny Christina (b. 1/9/1918 - d. 6/30/2001); Fischer, Jan, interviewer
INTERVIEW DESCRIPTION - This is the third of four interviews with Tina Hill conducted with Tina Hill in her central Los Angeles home. Hill basically directed the interviews and needed little coaxing, both giving details of her life experiences and also providing commentaries on them. When the interview was completed, Hill lamented that she had not had the chance to talk about her granddaughter, a story that rightfully needed to be told, and so a fourth interview was planned. 7/13/1980